On inert tracer modeling in a compound open channel - Chatila, Jean G. (1998)
This study investigates the impact on the pollutant transport and mixing processes of strong lateral momentum transfer effects associated with severely compound flow fields. Consideration was limited to conservative, non-buoyant material represented by a (dye) tracer. The experiments include measurements of dye concentrations downstream from steady-injection point source(s). In general, it is not possible to obtain analytical solutions to the dispersion equation in natural waterways with arbitrary boundary conditions. However, a variety of simplified solutions exists for idealized situations, which can be useful in obtaining order-of-magnitude estimates. These solutions were applied to our experimental data.